USING MEDITATION AND REFLECTION IN THE UNIVERSE LEADS TO ENHANCE OF CREATION AND CREATIVITY FOR HIGHER EDUCATION STUDENTS - Mahgoub, Yassir M; Abdul- Wahab, Faisal M (European Scientific Journal, ESJ, 2014)
This paper studies using meditation and reflection in the universe leads to enhance of creation and creativity for higher education students. Descriptive, analytical and experimental methods are used in this research. The results of the study are expected to be beneficial for the development of students’ performance in higher Education. The study sample consists of 30 students of the third level, batch 2012 – 2013, from the faculty of Education at the University of Khartoum: Republic of the Sudan. The results of the study are expected to be beneficial for using meditation and reflection on higher education programs. The study sample consists of Students totaling (30) students of the third level, batch (2012 – 2013) from faculty of Education of the University of Khartoum - Republic of the Sudan. There are topics for using of meditation and reflection were prepared depending on universe involves the extended abstract outcomes of learning like – hypothesizing, synthesizing, reflecting, generating ideas, applying the known to ‘far’ domains,’ working with problems that do not have unique solutions. The results showed there is a significant difference between experimental and control group, which confirms that the using meditation and reflection in the universe leads to enhance of creation and creativity for higher education students. The researchers recommended the students should be encouraged to arts education as an integral part of national development policies and devote substantial financial resources thereto. And set up arts education departments in higher education institutions.